Analisis Perilaku Modeling pada KPop Idols terhadap Self Image Remaja (Jurnal Bimbingan dan Konseling Islam, 2022)
This research aims to explain and determine the modeling behavior of K-Pop Idols on self-image. The purpose of this research is to see how the behavior of a model or someone who is considered a role model can affect adolescent self-image. This study uses a descriptive qualitative research method with a questionnaire model and literature study. Sources of data used are primary and secondary data where primary data is obtained directly through analysis and observation of questionnaires, while secondary data is obtained through literature study. The results of this study indicate that the modeling behavior of K-Pop Idols on adolescent self-image changes the way teenagers view their self-image. They become things in life; how to dress, how to talk, how to speak, etc.